Kecerdasan Emosional dalam Komunikasi Interpersonal - Zulqaidah, Zulqaidah; Hasriyati Harahap; Nurroyian; Rama Satya Tanjung; Dian Pratiwi Br. Marpaung; Aswaruddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Emotional intelligence is increasingly receiving attention in various fields, such as psychology, education, and self-development. This research uses a literature review method, specifically the Systematic Literature Review (SLR) approach, which aims to identify, evaluate and interpret research results related to the topic of interpersonal communication. This research aims to analyze the role of emotional intelligence in the world of education. Research findings show that emotional intelligence has an important role in improving social interactions, managing stress, and motivating students, which ultimately impacts students' academic achievement and mental well-being. Therefore, this research recommends integrating the development of emotional intelligence into the educational curriculum to create an effective learning environment and support students' holistic development.